2015
DOI: 10.1103/physreve.91.043017
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional transition after wake deflection behind a flapping foil

Abstract: We report the inherently three-dimensional linear instabilities of a propulsive wake, produced by a flapping foil, mimicking the caudal fin of a fish or the wing of a flying animal. For the base flow, three sequential wake patterns appear as we increase the flapping amplitude: Bénard-von Kármán (BvK) vortex streets; reverse BvK vortex streets; and deflected wakes. Imposing a three-dimensional spanwise periodic perturbation, we find that the resulting Floquet multiplier |μ| indicates an unstable "short waveleng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 36 publications
7
39
0
Order By: Relevance
“…Beyond the inverted vKm transition, for StA > 0.28, the wake is deflected from the horizontal centre line and C D becomes negative. The results shown that the distance between the tail of the foil and the point of deflection seems to decrease as StA increases, in agreement with the numerical simulations made by Deng and Caulfield (2015) (see figures 5(b), (c), (f) and (g)). For Re = 255, the performed simulations shown that the wake deflects when StA > 0.23, in good agreement with the 3D experimental observations of Godoy-Diana et al (2008) and the numerical simulations of He et al (2012) and Deng and Caulfield (2015).…”
Section: A Fixed Flapping Foilsupporting
confidence: 89%
“…Beyond the inverted vKm transition, for StA > 0.28, the wake is deflected from the horizontal centre line and C D becomes negative. The results shown that the distance between the tail of the foil and the point of deflection seems to decrease as StA increases, in agreement with the numerical simulations made by Deng and Caulfield (2015) (see figures 5(b), (c), (f) and (g)). For Re = 255, the performed simulations shown that the wake deflects when StA > 0.23, in good agreement with the 3D experimental observations of Godoy-Diana et al (2008) and the numerical simulations of He et al (2012) and Deng and Caulfield (2015).…”
Section: A Fixed Flapping Foilsupporting
confidence: 89%
“…To investigate the nonlinear development of the identified unstable Floquet modes, we use a finite volume numerical code to solve the fully nonlinear threedimensional Navier-Stokes equations. This code has been applied to both a flapping airfoil [32][33][34], and an oscillating elliptical foil [35]. We ensure that the Courant number of all cells is less than one, and that each oscillation period T is decomposed into at least 2000 time steps so that the unsteadiness caused by the oscillation is well-resolved.…”
Section: B Numerical Methodologymentioning
confidence: 99%
“…Unlike traditional Bénard-von Kármán (BvK) vortex streets viewed in a two-dimensional plane (Deng and Caulfield 2015), here the flow wakes produced by the forked tail (caudal fin) show strongly three-dimensionality. Nevertheless, the reversed BvK streets signaling propulsive wakes can still by observed.…”
Section: Validationmentioning
confidence: 76%